Decision Support System For Selection Of The Best Corn Seeds Using The Simple Additive Weigthing Method - Triyanto Triyanto; Theo W. M. L. K. Gusbager; Elvis Pawan; Patmawati Hasan (International Journal of Computer and Information System (IJCIS), 2023)
Corn is a type of plant that has many benefits, corn plants can be found in various parts of the world, including Indonesia. This plant also spreads throughout Indonesia and in several areas becomes a staple. The Keerom district area of Papua province is very easy to find corn plants. With the high demand for corn, many farmers plant corn. However, it is not uncommon for farmers to experience crop failure because they are influenced by many factors, such as the type of seeds planted that are not good seeds. This study aims to design a decision support system using the SAW method. This research resulted in an application that is able to provide recommendations for types of seeds to farmers in rankings. The SAW method was chosen because it has characteristics that are in line with the recommendation technique which makes it easier for farmers to determine the choice of seeds. The test results using the blackbox method obtained a suitability value of 100% of all forms tested